Facile Entry to Pharmaceutically Important 3-Difluoromethyl-quinoxalin-2-ones Enabled by Visible-Light-Driven Difluoromethylation of Quinoxalin-2-ones - Kai-Zhong Fu; Xu-Xin Chen; Ya-Shi Zhao; Yuan-Qing Gu; Guo-Kai Liu (MDPI AG, 2022)
CF2H moiety has a significant potential utility in drug design and discovery, and the incorporation of CF2H into biologically active molecules represents an important and efficient strategy for seeking lead compounds and drug candidates. On the other hand, quinoxalin-2-one is of great interest to pharmaceutical chemists as a common skeleton frequently occurring in plenty of natural products and bioactive compounds. Herein, we reported a practical and efficient protocol for the synthesis of 3-CF2H-quinoxalin-2-ones. Thus, in the presence of 3 mol% of photocatalyst and S-(difluoromethyl)sulfonium salt as difluoromethyl radical sources, a wide range of quinoxalin-2-ones readily underwent a visible-light redox-catalyzed difluoromethylation reaction, to deliver structurally diverse 3-difluoromethyl-quinoxalin-2-ones. We believe that this would facilitate increasing chances and possibilities for seeking potential lead compounds and drug candidates and further boost the development of fluorine-containing pharmaceuticals.